Ergonomic Risk Assessment on Palm-Oil Harvesting Workers in East Kalimantan - Theresia Amelia Pawitra; Lina Dianati Fathimahhayati; Farida Djumiati Sitania (Jurnal Kesehatan Masyarakat, 2025)
Along with the growth of the palm-oil industry in Indonesia, work-related musculoskeletal disorders (WMSD) experienced by palm-oil harvesting workers also increased. This paper aims to evaluate ergonomic risk factors among harvesting palm workers in East Kalimantan and to propose suggestions to mitigate the risks. A total sample of 70 workers from 3 plantations in Muara Wahau, Babulu, and Muara Badak was observed in 2023. Gotrak survey and ergonomic risk factor (ERF) questionnaire of SNI 9011:2021 were utilized for determining the WMSD and identifying the ergonomics risk, respectively. The result showed that 91% of workers experienced pain after work, and 72% frequently experienced physical fatigue. The Gotrak survey on cutting and carrying bunches activity revealed high exposure risk for the neck (97%), followed by the shoulder (77%) and knee (55%). Meanwhile, during the activity of loading bunches onto the truck, high exposure risk occurs in the shoulders (73%), elbows (53%), and knees (53%). The result of the Kruskal-Wallis statistical test indicates that there is a difference in Gotrak levels among the three locations. The Gotrak level in Muara Wahau is the highest, followed by Babulu and Muara Badak. The results of the ERF questionnaire showed that loading to truck, followed by carrying FFB to the fruit collection point, were the two activities with high ERF scores, i.e., 39 and 34, respectively. Finally, improvements such as stretching exercises before and during work, as well as redesigning ergonomic T-hook and egrek, will mitigate the risk.